ERS Early Career Members meet EAACI Junior Members: the launch of a strong, fruitful collaboration. Issue 3 (September 2017) - Mathioudakis, Alexander G.; Eguiluz Gracia, Ibon; Bartel, Sabine; Tsilochristou, Olympia
Training, development and support in the career progression of junior members are of utmost importance and represent high priorities for both the European Respiratory Society (ERS) and the European Academy of Allergy and Clinical Immunology (EAACI). Apart from clinical and research fellowships, and educational events, both societies have invested in their respective juniors' boards. These aim to highlight the needs of the juniors, organise educational activities targeted to young clinicians and scientists, and promote active participation of early career members in the respective society's activities. Both ERS Early Career Members Committee (ECMC) and EAACI Junior Members' Assembly (JMA) board have been very active over past years, which has led numerous initiatives. Learn about the collaboration between @EarlyCareerERS and @EAACI_JM http://ow.ly/WUTO30d7dpC